High-voltage modulator of the Linac injector with voltage pulse stabilization - Anokhin, R.A.; Dubniuk, S.N.; Gaponenko, N.I.; Kobets, A.P.; Kravchenko, A.I.; Manuilenko, O.V.; Reshetnikov, V.N.; Shevchenko, A.S.; Soshenko, V.A.; Svichenskiy, V.G.; Zajtsev, B.V.; Zabotin, A.V.; et al. (Вопросы атомной науки и техники, 2019)
The high-voltage pulse modulator based on the modern semiconductor elements is described. The modulator is intended for use in the power supply system of LINAC helium ions injector and has the ability to smoothly adjust the amplitude (110…150 kV) and the pulse duration (0.5…1 ms). The use of a pulse-to-peak stabilization scheme, made on the basis of a parametric stabilizer with parallel switching of the load, made it possible to increase the accelerated current at the accelerator output by 2 times. Описано високовольтний імпульсний модулятор, виконаний на сучасній напівпровідниковій елементній базі. Модулятор призначений для використання в системі живлення інжектора лінійного прискорювача іонів гелію. Модулятор дозволяє плавно регулювати амплітуду (110…150 кВ) і тривалість імпульсу (0,5…1 мс) напруги. Використання схеми стабілізації імпульсу напруги, виконаної на основі параметричного стабілізатора з паралельним перемиканням навантаження, дозволило збільшити прискорений струм пучка на виході прискорювача в 2 рази. Описан высоковольтный импульсный модулятор, выполненный на современной полупроводниковой элементной базе. Модулятор предназначен для использования в системе питания инжектора линейного ускорителя ионов гелия. Модулятор позволяет плавно регулировать амплитуду (110…150 кВ) и длительность импульса (0,5…1 мс) напряжения. Использование схемы стабилизации импульса напряжения, выполненной на основе параметрического стабилизатора с параллельным переключением нагрузки, позволило увеличить ускоренный ток пучка на выходе ускорителя в 2 раза.